Conceptual and methodological issues in defining and measuring absolute poverty - Chiara Saraceno (Rivista Italiana di Economia Demografia e Statistica, 2024)
The notion of absolute poverty recalls that of basic needs, which, however, is far from having a consensual meaning. The author first discusses two main contrasting definitions of basic needs - one based on an idea of pure subsistence, the other based on human rights and the capability approach. The author then outlines the conceptual and methodological issues involved in intra- and cross country as well as over time comparison. In the final paragraph, the~ author suggests that in order to overcome the limitations of any poverty measure that ignores intra- and cross-country differences in access to human and social rights and in the availability of common goods, the author suggests that survey-based data on income or consumption should be integrated with data on selected functionings at the individual and household level (e.g., education, health, housing), which in turn should be contextualized based on the national and local availability and accessibility of public goods that are defined as essential for supporting those functionings.
Keywords: 330